Collembola population in revegetated tin-mined lands in Bangka Island - EDDY NURTJAHYA; DEDE SETIADI; EDI GUHARDJA; MUHADIONO MUHADIONO; YADI SETIADI (Society for Indonesian Biodiversity, 2007)
Several indicators used to evaluate revegetation programs are survival, plant growth, root growth, cover, litter production, natural recolonisation, habitat improvement, microbes, insects, and birds. To study the prediction of the potency of Collembola as bioindicator of revegetated tin-mined lands, population densities on revegetated tin-mined lands under Acacia mangium stands at 0, 3, 7, 9, 12, and 13- years old were measured using pitfall trap method. It was recorded four Collembola species i.e. one belongs to family Isotomidae, two to family Entomobryidae, and one to family Sminthuridae. Population density of Collembola spp. in unrevegetated tin-mined land (0-year old) was significantly different to those in revegetated tin-mined lands. Although population density was higher in the older revegetated tinminedlands with the highest density recorded in 13-year old site (4816 ind. m-2), densities among revegetated tin-mined lands were notsignificantly different. The different population density appears related to organic material, litter either from revegetated plant, or from plant invaders during succession, and soil humidity. This study confirms the prediction of the potency of Collembola population density as bioindicator of revegetated tin-mined lands under Acacia mangium stands.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: , Collembola, bioindicator, revegetation, tin tailing, Bangka